Family Policy as a Social Investment: An Effort to Initiate the Decentralization of Social Policy in Indonesia - Taufiq, Ahmad; Fadli, Moh.; Putra, Fadillah; Badriyah, Nurul (Wacana Journal of Social and Humanity Studies, 2023)
Three paradigms enliven the implementation constellation of the welfare state — social democracy paradigm, neo-liberal paradigm, and social investment paradigm — Although they have been tough enough to guide many countries in the world to this point in formulating social policies for the welfare of their citizens, they pay less attention to environmental perspective and local capacity to innovate, particularly in the formulation of family policy.  This paper wants to point out that one of the paradigms mentioned earlier, specifically the social investment paradigm, can be used to strengthen the idea of decentralization and that environmental policy is also a social policy based on proper family policy since social investment aims to overcome new social risks and the needs of post-industrial society; such as seeking solutions for working and family life relationships, single parents, and low or even outdated life skills. The main notion of this viewpoint is that social policy should have productive instead of redistributive potential, which is necessary for economic development and employment growth. Through the concept of life course, the family becomes an irreplaceable unit of the social investment paradigm’s policy because a human’s life course has traditionally always been through a receptacle called family. The social investment policy is about serving and providing the greatest benefits at every stage of the life course however, in the perspective of Indonesia, the social investment approach in social policy has not yet entered the mainstream of the decentralization movement in this country after the reform, though it is realized that decentralization has fostered social capital and civic tradition at the local level. Keywords: welfare state, social policy, environmental policy, family policy, social investment, decentralization